Strategic Human Resource Management dan Kinerja Perusahaan: Kajian Teoritik dari Perspektif Kontinjensi - Temengkol, Maria Goretti (Kajian Manajemen dan Bisnis, 2011)
Previous literature states that companies can achieve competitive advantage through the strategic management of human resources, which is also known as strategic human resource management. Universalistic perspective emphasizes that human resource capabilities can help companies gain competitive advantage with the practices of human resource management that encourages a focus on the customer. However, it is not clear under what conditions firms use the Strategic human resource management to improve organizational performance. "The purpose of this article is to discuss the role of strategic human resource management in improving organizational performance from the perspective of contingency.